한국 청소년의 구강건강행태와 구강보건교육 경험의 실태 - 오현경; Hyun Kyung Oh; 송윤신; Yun Shin Song; 안소희; So Hee An; 천성수; Sung Soo Chun (Han'guk Ch'iwisaeng Hakhoe chi, 2015)
Objectives: The objective of the study is to investigate oral health behavior and oral health education experience in Korean adolescents from the ninth(2013) web-based survey of Korean youth risk behavior. Methods: The subjects were 72,435 students through the ninth 2013 web-based survey of Korean youth risk behavior conducted by the Ministry of Education, Science, and Technology, the Ministry of Health and Welfare, and the Korea Centers for Disease Control. The questionnaire consisted of socio-demographical characteristics of the subjects, oral health behavior, and oral health education experience. Data were analyzed by SPSS 18.0 program. Results: Oral health education had much influence on tooth brushing after lunch, oral cavity disease prevention, sealants, fluoride application, scaling experience, and consumption of vegetables, milk, carbonated soft drinks, noodles, and snacks. The oral health education had a great impact on those who took good oral health behavior into action. Conclusions: It is very important and necessary to develop the continuing effective oral health education program for the adolescents and make them tale into action.